2022
DOI: 10.1111/ene.15495
|View full text |Cite
|
Sign up to set email alerts
|

Current management of acute ischemic stroke in Africa: A review of the literature

Abstract: Stroke is one of the leading causes of disability, dementia, and mortality worldwide. It is a medical emergency characterized by the interruption or reduction of the flow through brain blood vessels, leading to poor perfusion of brain tissue [1]. The three main types of stroke are ischemic stroke, hemorrhagic stroke, and transient ischemic attack. Whereas the global age-standardized stroke mortality rates reduced remarkably between the years 1990 and 2016, the opposite took place in Africa, which has witnessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…Canine visceral leishmaniasis (CVL) plays a vital role in the continuance of transmission levels and the dissemination of the disease, particularly in urban areas [ 8 , [22] , [23] , [24] , [25] ]. Therefore, successful control of this disease is an onerous task.…”
Section: Current Efforts and Challenges Facing Responses To Leishmani...mentioning
confidence: 99%
“…Canine visceral leishmaniasis (CVL) plays a vital role in the continuance of transmission levels and the dissemination of the disease, particularly in urban areas [ 8 , [22] , [23] , [24] , [25] ]. Therefore, successful control of this disease is an onerous task.…”
Section: Current Efforts and Challenges Facing Responses To Leishmani...mentioning
confidence: 99%
“…Raising awareness of the causes and transmission mechanisms of leptospirosis and its epidemiology among healthcare workers and the general population is mandatory as an important strategy for the control and prevention of the disease [ 15 , [19] , [20] , [21] ]. This can be done effectively through mass education within the community by initiating public awareness campaigns, social media posters, and television and radio sessions addressing proper control and preventive measures [ 22 , 23 , 30 ].…”
Section: Recommendationsmentioning
confidence: 99%
“…In addition to the usual symptoms of CD (i.e., fever, fatigue, body ache, headache), co-infection with COVID-19 contributed to dysregulated immunothrombosis, triggering a considerable change in management as anticoagulants were now included [ 6 , 15 ]. Some studies also suggested possible cardiovascular involvement as a complication in co-infected patients, putting individuals at greater risk of prolonged hospitalisation and increased mortality [ 2 ].…”
Section: The Current Status Of Chagas Disease Amidst the Covid -19 Pa...mentioning
confidence: 99%
“…CD and the COVID-19 pandemic are both multi-systemic diseases that can impact various internal organs, including the cardiovascular, central nervous [ [13] , [14] , [15] , [16] , [17] , [18] ], and digestive systems [ 4 ].…”
Section: Challenges Facing Responses To Chagas Disease During Covid-1...mentioning
confidence: 99%
See 1 more Smart Citation